Primary malignant melanoma of the esophagus - Ling, Chunxiang; Feng, Jizhen; Li, Jiamei; Liu, Qingwei (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Ling C, Feng J, Li J, Liu Q. Primary malignant melanoma of the esophagus. Turk J Gastroenterol 2018; 29: 711-3.